Numerical and Experimental Efficiency Evaluation of a Counter-Rotating Vertical Axis Wind Turbine - Malael, I.; Dragan, V. (Engineering, Technology & Applied Science Research, 2018)
This paper investigates the concept of a concentric counter-rotating vertical axis wind turbine (VAWT), consisting of a two stage vertical H-type turbine with three blades on each stage. The model has an inner and an outer stage, rotating in opposition to each other. Both numerical and experimental tests have been performed in order to validate this new concept. Numerical analysis is based on the use of 2.5-dimensional, unsteady simulations using a DOF type of analysis which allows for the two stages to self-adjust their rotation speed. Sliding mesh conformal interfaces are defined between these subdomains to minimize numerical artifacts such as artificial relations or entropy changes. Fully turbulent URANS were carried out in Ansys Fluent software. One key outcome was the momentum coefficient for each stage at different tip wind speed values. Another, more qualitative, outcome is the analysis of vortex shedding, impingement and overall interaction between the stages at different positions and scenarios. Ultimately, the numerical results have been validated using a scaled experimental device which was analyzed in the wind tunnel at different free stream speeds.